13.3: A new pixel structure for OLEDoS micro‐display. (4th October 2019) - Guo, Aiying; Ran, Feng; Zhang, Jianhua
Abstract : In this paper, we propose a new pixel structure for the organic Light Emitting Diode (OLED) 0.65 inch SVGA resolution micro‐display with 8 bit gray level. The proposed pixel structure is composed of 4 MOSFETS and one capacitor to integrate the pixel structure in the restricted pixel area (9um×9um) using 0.18um technology. The simulation result shows that the maximum error of emission current occurs at high gray level.